2017
DOI: 10.3389/fnhum.2017.00122
|View full text |Cite
|
Sign up to set email alerts
|

Living in the Fast Lane: Evidence for a Global Perceptual Timing Deficit in Childhood ADHD Caused by Distinct but Partially Overlapping Task-Dependent Cognitive Mechanisms

Abstract: Dysfunctions in perceptual timing have been reported in children with ADHD, but so far only from studies that have not used the whole set of timing paradigms available from the literature, with the diversity of findings complicating the development of a unified model of timing dysfunctions and its determinants in ADHD. Therefore, we employed a comprehensive set of paradigms (time discrimination, time estimation, time production, and time reproduction) in order to explore the perceptual timing deficit profile i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 58 publications
(130 reference statements)
2
27
0
Order By: Relevance
“…The attention-deficit hypothesis has been discussed in the context of ADHD ( 120 ). The timing deficit hypothesis, which has been mainly verified as the etiology of ADHD ( 121 ), has also been suggested to underlie DCD ( 122 ). However, several studies investigating the automatization deficit of DCD also reported negative results ( 16 , 123 127 ).…”
Section: Discussionmentioning
confidence: 99%
“…The attention-deficit hypothesis has been discussed in the context of ADHD ( 120 ). The timing deficit hypothesis, which has been mainly verified as the etiology of ADHD ( 121 ), has also been suggested to underlie DCD ( 122 ). However, several studies investigating the automatization deficit of DCD also reported negative results ( 16 , 123 127 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, WM should be crucial only for timing performance from about 1 s and longer, when temporal characteristics of the experimental stimuli have to be analysed and information has to be held in mind until the comparison stimulus is displayed. Beyond WM, time discrimination performance in children and adolescents with ADHD was associated with measures of attention and impulsivity, but only in studies using longer stimulus presentation durations5 14 and longer ISI 17. In addition, we suggested delay aversion and its secondary adaptations, that is, the motivational tendency to escape from delay by investing less time in a task if this helps to reduce overall experimental duration,18 as a further potential predictor of disturbed timing processes in ADHD.…”
Section: Introductionmentioning
confidence: 77%
“…The latter, in contrast, require additional cognitive resources, as they ask the child to provide a verbal duration estimation of a previously presented stimulus (time estimation), to produce a previously specified time interval, for example, by pressing a response button (time production), or to infer the duration of a stimulus that had been previously presented for a defined time interval and to indicate this time interval subsequently by pressing a response button (time reproduction). Based on our experimental findings using these four paradigms,5 we recently proposed a model of disturbed perceptual timing in children with ADHD, consisting of two distinct but partially overlapping neurocognitive mechanisms: (i) working memory (WM) and attention processes that cause time estimation and time production deficits and (ii) WM and motivational processes that cause time reproduction deficits. Moreover, we found time discrimination deficits in these children as well, but these deficits were not explained by our predictor variables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceptual timing tasks include paradigms operating in the range of several seconds where participants are asked (1) to provide a verbal duration estimation of a previously presented stimulus (time estimation paradigm), (2) to produce a previously specified time interval by pressing a button (time production paradigm), (3) or to reproduce the duration of a previously presented stimulus by pressing a button (time reproduction paradigm), as well as (4) time discrimination paradigms where participants have to discriminate between stimuli that differ in their duration by tens or hundreds of milliseconds.…”
Section: Introductionmentioning
confidence: 99%